Semantic and grammatical parameters of the homocomplex as - Джочка, Ірина Федорівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2021)
The relevance of the research is due to the increased attention of linguists to grammatical homonymy. Within the framework of grammatical homonymy, morphological, interpart-of-speech and syntactic homonyms are distinguished. The focus is on the problems of part-of-speech homonymy, in particular on the phenomenon of morphological syncretism due to the ambiguity of structural and semantic features of parts of speech and changes of the morphological status of certain words in different syntagmatic environments. Changes in the categorical-semantic meaning of the lexical unit as, synonymous series of components of the specified sound complex, the nature of the syntagmatic environment, syntactic functions, positional fixation in a certain syntax unit, functional phraseology in compound conjunctions and particles are described. The conceptual scope of the term „homocomplex” is considered, it is defined as a sound complex, which is used to denote the title of a group of functional homonyms and words of the zone of syncretism. It is established that the homocomplex as is represented by three grammatical homonyms such as adverb, conjunction and particle. The source word for the formation of derivatives of the conjunction and particle is the adverb as. In the syntactic position of the adverb, this lexical unit appears in the adverbial position, expressing the following meanings: the question of manner (how?); the degree of detection of an action, state (very, extremely); mode of action (how); time of action (when); indefinite way (somehow). In the syntactic sphere of the conjunction, losing the ability to express a sign, the lexical unit „how” often serves as a means of expressing comparative semantic-syntactic relations; forming phraseologized compounds, it can act as an expression of clauses of condition, time and concession. Not denoting defining and adverbial meanings and not combining parts of a compound sentence, the lexical unit as belongs to the class of particles. A typical function of this particle is an amplifying one. It is complemented by additional semantic shades of meaning, such as „very”, „extremely”, „suddenly”, etc., which serve to express the speaker’s surprise, indignation, dissatisfaction, surprise, and others.